Початок кримінального провадження у формі приватного обвинувачення: постановка проблеми - Власова, Г.; Vlasova, H. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено питання щодо початку кримінального провадження у формі приватного обвинувачення. Виокремлено критерії, які в умовах сучасного кримінального процесуального законодавства України слугують підставами для віднесення заяви потерпілого до справ приватного обвинувачення. З урахуванням виявлених недоліків сформовано пропозиції по подальшому удосконалення інституту кримінального провадження у формі приватного обвинувачення. In the article the criteria, which in the conditions of modern criminal procedure legislation of Ukraine become reasons for concerning the victim’s plaint to the cases of private charge, have been investigated. It has been concluded that the demands of legislator regarding the time of the beginning of criminal proceeding in the form of private charge are not made quite successfully. For an investigator (prosecutor) a plaint of a victim about the commission of a criminal offence against him according to points 2, 3 part 1 of the article 477 of the Criminal Procedure Code of Ukraine, does not mean automatic implementation of the criminal proceeding exactly in the form of private charge, even if the victim points at the subject of the crime. At the same time one of the approaches, that can solve these problems, concerns investigator’s (prosecutor’s) procedural decisions during investigation before trial. For example, criminal proceeding concerning the use of coercive measures of medical kind also refers to special rules of criminal proceeding. However, in part 2 of the article 503 of the Criminal Procedure Code of Ukraine the legislator emphasized that if during the before trial investigation the reasons for implementation of criminal proceeding about the use of coercive measures of medical type are established, the investigator, (prosecutor) makes a decision about the change of before trial investigation order, and continues it according to special rules, established in the article 39 of the Criminal Procedure Code of Ukraine.
Beginning of Criminal Proceeding in the Form of Private Charge: Formulation of the Problem
Keywords: кримінальний процес; приватне обвинувачення; заява потерпілого; початок провадження; criminal process; private charge; plaint of a victim; the beginning of proceeding